The effect of internal endpoint temperature on smoked sausage quality stored under light emitting diode and fluorescent lighting - Gaschler, Alicia Jo (Kansas State University, 2012)
Quality attributes of vacuum packaged, skinless smoked sausage made with a combination of pork, turkey, and beef, cooked to 64, 68, or 72°C internal endpoint temperature following USDA FSIS Appendix A, and displayed at 4°C for up to 120 days under light emitting diode (LED) and fluorescent (FLS) lighting were evaluated. External color, pH, thiobarbituric acid reactive substances (TBARS), proximate analysis, reheat yield, and sensory attributes were measured on day 0, 90, and 120 of display. Purge amount and color were measured on day 10, 90, and 120. Product was displayed in LED or FLS retail display cases set to the same operational and temperature profiles. Lighting type had no effect (P>0.05) on any of the measured attributes. Instrumental external color was less (P<0.05) red by 0.63 units in product thermally processed to 64°C than product processed to 68°C. Product cooked to 72°C was less (P<0.05) yellow externally compared to those processed to 64 and 68°C. Purge color lightness increased (P<0.05) in product thermally processed to 72 compared to 64°C. Purge was more red by 0.36 units (P<0.05) on day 120 compared to day 10. Yellowness of purge color increased at 72°C compared to 64°C by 0.66 units. Purge was more yellow (P<0.05) on d 120 compared to d 10 and 90. TBARS values decreased (P<0.05) from 0.70 mg of malonaldehyde/100g on day 0 to 0.35 and 0.23 on d 90 and 120, respectively. Sensory panel scores showed that flavor intensity decreased (P<0.05) as day of storage increased, and saltiness decreased from d 0 to d 90. Purge content increased (P<0.05) from 1.45% to 1.90% in products cooked to 64 and 68°C, respectively. The amount of purge increased (P<0.05) from 1.58% to 1.92% on day 10 and 90, respectively. While there were slight changes found in quality characteristics of smoked sausages during storage, many of these were minimal. Processors could reduce their internal endpoint temperature following USDA FSIS Appendix A guidelines with minimal effect on product quality. Vacuum packaged pre-cooked smoked sausages could be displayed under LED or FLS lighting with no effect on product quality.
Keywords: Internal endpoint temperature; Lighting; Sausage; Animal Sciences (0475)